Comparative Acceptability and Perceived Clinical Utility of Monitoring Tools: A Nationwide Survey of Patients with Inflammatory Bowel Disease. Issue 8 (August 2017) - Buisson, Anthony; Gonzalez, Florent; Poullenot, Florian; Nancey, Stéphane; Sollellis, Elisa; Fumery, Mathurin; Pariente, Benjamin; Flamant, Mathurin; Trang-Poisson, Caroline; Bonnaud, Guillaume; Mathieu, Stéphane; Thevenin, Alain; et al.
Abstract : Background: Objective control of intestinal inflammation during inflammatory bowel disease (IBD) is becoming the main driver for medical treatment. However, the monitoring tools-related burden remains poorly investigated. We aimed to evaluate their comparative acceptability and utility according to patients with IBD. Methods: After a preliminary phase, the final questionnaire encompassing self-administered and physician questionnaires was prospectively and consecutively submitted to 916 patients with IBD from 20 public and private centers. Acceptability and utility visual analog scales (VAS) were expressed as median with interquartile range. Results: Regarding the group of patients with Crohn's disease (n = 618), venipuncture (VAS = 9.3 [8.8–9.7]) and ultrasonography (VAS = 9.3 [8.7–9.7]) were the most acceptable tools ( P < 0.0001, for each comparison), whereas rectosigmoidoscopy was the least acceptable tool (VAS = 4.4 [1.2–7.3]) ( P < 0.0001, for each comparison). Wireless capsule endoscopy (VAS = 8.5 [5.2–9.3]), magnetic resonance enterocolonography (VAS = 8.0 [5.0–9.2]), and stools collection (VAS = 7.7 [4.6–9.3]) were more acceptable than colonoscopy (VAS = 6.7 [4.3–8.9]) ( P < 0.0001, for each comparison). The acceptability was assessed in 298 patients with ulcerative colitis for venipuncture (VAS = 9.4 [8.8–9.7]), stools collection (VAS = 8.1 [5.7–9.4]), colonoscopy (VAS = 7.5 [4.7–9.2]), and rectosigmoidoscopy (VAS = 6.7 [2.8–9.1]); ( P < 0.001 for each comparison). All monitoring tools were considered as highly useful by patients with IBD. Decreased acceptability was related to embarrassment for the collection/transport of stools (60.7%), bowel cleansing (76.3%) for colonoscopy, abdominal discomfort (51.3%) and rectal enema (36.6%) for rectosigmoidoscopy, bowel distension (48.3%) for magnetic resonance enterocolonography, and potential capsule retention (21.4%) for wireless capsule endoscopy. Conclusions: Among the IBD monitoring tools, endoscopy demonstrated the lowest acceptability supporting the development of alternative modalities. Patients' information and examination conditions should be improved to ensure proper monitoring adherence. Abstract : Article first published online 24 May 2017.